2016
DOI: 10.5812/ircmj.36226
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Dyslipidemic Properties of Saffron: Reduction in the Associated Risks of Atherosclerosis and Insulin Resistance

Abstract: Background: Recently herbs considered as biological and safe agents to treat, control and prevent of many health problems such as obesity and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 25 publications
5
26
1
Order By: Relevance
“…These saffron based by-products need to be tested to assess its pharmacological applications. Bioactive compounds from petals have shown antinociceptive, anti-inflammatory [31], cytotoxic, antimicrobial, antioxidant, antidiabetic [32], antiobesity [33], antidepressant [34], anticancer, antityrosinase properties, as well as reduce blood pressure and contractility [35]. Several phenolic compounds from saffron leaves have been identified, showing antibacterial [36,37], anticancer [30], antioxidant, and metal ion chelating activities [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…These saffron based by-products need to be tested to assess its pharmacological applications. Bioactive compounds from petals have shown antinociceptive, anti-inflammatory [31], cytotoxic, antimicrobial, antioxidant, antidiabetic [32], antiobesity [33], antidepressant [34], anticancer, antityrosinase properties, as well as reduce blood pressure and contractility [35]. Several phenolic compounds from saffron leaves have been identified, showing antibacterial [36,37], anticancer [30], antioxidant, and metal ion chelating activities [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…There is a general consensus on the positive, supporting role of saffron, or its active constituents, in modulating serum total cholesterol, total triglyceride (TG), low-density lipoprotein (LDL) cholesterol, and high-density lipoprotein (HDL) cholesterol (Arasteh et al, 2010;Hoshyar et al, 2016;Samarghandian, Azimi-Nezhad, & Samini, 2014;Shirali et al, 2013). In an in vitro study, crocetin decreased the levels of reactive oxygen species, free radical-mediated lipid peroxidation, and increased radical scavenging activity (Xiang et al, 2006).…”
mentioning
confidence: 99%
“…They concluded that the extract of saffron petals reduced total cholesterol, triglyceride and LDL and increased HDL levels and reduced leptin and insulin levels. Therefore, they concluded that saffron extract increases antioxidant levels and decreases the lipid peroxidation 74…”
Section: Discussionmentioning
confidence: 99%